Atherosclerotic Fibrous Plaques in Women Present ECM Remodeling Linked to TGF-β. - Sakkers,TR; Mili,E; Winter,H; Kapteijn,D; Perry,RN; Barbera,N; Watts,K; Dias,IR; Meteva,D; Wesseling,M; Mol,BM; de,Borst GJ; et al. (Circ Res, 2026)
BACKGROUND: Sex and atherosclerotic plaque histology are intertwined, with fibrous plaques being more prevalent in women. Plaque erosion, a significant contributor to acute coronary syndromes, is linked to fibrous plaques and is more prevalent in women than men. We hypothesize that the molecular drivers of histologically determined fibrous plaques differ between men and women. METHODS: Human end-stage atherosclerotic plaques were isolated from carotid endarterectomy patients included in the Athero-Express Biobank. Fibrous plaques were histologically assessed, linked to clinical characteristics, and processed for protein, bulk RNA, single-cell RNA, and DNA methylation data. We leveraged sex-differential gene expression and deconvolution analyses to uncover sex-biased molecular and cellular mechanisms. Spatial transcriptomics localized gene expression patterns in plaques. Furthermore, we studied the female-biased processes in human plaque endothelial cells and vascular smooth muscle cells stimulated with TGF-β (transforming growth factor-β), with or without SMAD3 (SMAD family member 3) inhibition. RESULTS: Of 1889 atherosclerotic plaques (1309 male and 580 female), fibrous lesions were observed in 50% of female and 31% of male patients. Compared with patients with atheromatous plaques (n=494), women with fibrous plaques exhibited a high prevalence of smoking, while men with fibrous plaques presented more often with diabetes. Female fibrous plaques were characterized by smooth muscle cell-driven ECM (extracellular matrix) remodeling, TGF-β response, and endothelial-to-mesenchymal transition, localized to the fibrous cap. Conversely, male plaques were linked to macrophage-mediated inflammation proximal to the core, dependent on diabetes. Finally, we experimentally confirmed these female-biased mechanisms, showing that TGF-β induced endothelial-to-mesenchymal transition in endothelial cells and ECM remodeling in vascular smooth muscle cells, both part